A comparison of modelling and imagery in the acquisition and retention of motor skills - Ram, N.; Riggs, S. M.; Skaling, S.; Landers, D. M.; McCullagh, P. (Journal of Sports Sciences, 2007)
Although many researchers have examined the effects of imagery and/or modelling interventions, it is unclear which of the two interventions is more effective. In two experiments, novice learners assessed over multiple trials of a free weight squat lifting or a stabilometer balancing task were given modelling, imagery, a combination of modelling and imagery, or control interventions. Group differences indicated, in general, that groups receiving modelling (modelling, combination) evidenced a more appropriate form than groups that did not receive modelling (imagery, control). When apparent, these differences were already in place after the first of several interventions. Practical implications are that even a single bout of modelling can have immediate beneficial effects on movement form (Experiments 1 and 2) and outcome (Experiment 1).